2019
DOI: 10.1021/acsapm.9b00571
|View full text |Cite
|
Sign up to set email alerts
|

Production and Dynamic Mechanical Analysis of Macro-Scale Functionalized Polydicyclopentadiene Objects Facilitated by Rational Synthesis and Reaction Injection Molding

Abstract: is a ring-opening metathesis polymer derived from dicyclopentadiene. Valued for its light weight, excellent material strength, and good performance at both high and low temperatures, PDCPD is used to make body panels for tractors and heavy-duty trucks. We recently described the first functionalized form of PDCPD (fPDCPD) that maintains the thermal stability of the parent polymer. However, while commercial PDCPD components are produced through a reaction injection molding process on very large scale, our fPDCPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…30 mol %) . Other reports have noted similar increases in T g with increased crosslinking density or polar functionalization of DCPD itself. The addition of cleavable crosslinks to thermosets with permanent, noncleavable crosslinks, however, cannot facilitate chemical deconstruction into soluble products (Figure C) . Thus, additives that simultaneously enable thermoset deconstruction without compromising mechanical properties are elusive.…”
mentioning
confidence: 91%
“…30 mol %) . Other reports have noted similar increases in T g with increased crosslinking density or polar functionalization of DCPD itself. The addition of cleavable crosslinks to thermosets with permanent, noncleavable crosslinks, however, cannot facilitate chemical deconstruction into soluble products (Figure C) . Thus, additives that simultaneously enable thermoset deconstruction without compromising mechanical properties are elusive.…”
mentioning
confidence: 91%
“…Understanding the chemical properties of a novel material is paramount to discovering its possible future applications. Although some of the unique properties of f PDCPD have been reported previously by our group, [18][19][20] the degree to which the surface can be further functionalized is not yet completely understood. For example, while previous work has shown that partial hydrolysis of the ester functional groups on the surface of f PDCPD can raise the surface energy, 18 we have not yet examined the installation of other functionality at this position.…”
Section: Resultsmentioning
confidence: 88%
“…21 f PDCPD offers a tunable, elevated surface energy, and a higher T g compared with the parent material. 18 Importantly, both the thermal stability of f PDCPD (as assessed by thermogravimetric analysis) 18,19 and the storage modulus (measured by dynamic mechanical analysis) 20 were shown to be similar to those of the parent polymer. The introduction of new functionality while maintaining durability allows for further modifications, potentially increasing the applications of f PDCPD for industrial and biomedical use.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations